Effects of Generalism and Niche Overlap on Network Linkages Among Youth Service Agencies - Wholey, Douglas R.; Huonker, John W. (Academy of Management Journal, 1993)
From one theoretical perspective, exchange, dissimilar organizations link together because they must acquire needed resources from each other. From another perspective, homophily, similar organizations link together to cooperate. We examined predictions based on both perspectives concerning the effects of generalism and niche overlap on interorganizational linkages among 46 youth service agencies. Generalism and niche overlap were measured for clients, services, and funding. The results support the argument that similar organizations link more than the argument that dissimilar organizations link and suggest that homophily is an important determinant of interorganizational networks.